The Quality of Beef at Traditional Market in Poncokusumo Subdistricts Malang Regency - Dedes Amertaningtyas (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2013)
The purposes of this study were to determine the physical quality of beef sold by traders fresh beef such as water content, pH, water holding capacity (WHC), cooking loss or shrinkage cooking and texture or tenderness. The research material was five samples of fresh beef sold to traders in traditional markets Poncokusumo Distric of Malang Regency. The method used was an experiment using completely randomized design (CRD). Samples of fresh beef were obtained from 5 traders fresh beef sellers in traditional markets Poncokusumo Distric of Malang Regency. The variables this research were physical quality such as water content ( % ), pH, water holding capacity (WHC) ( % ), cooking loss or shrinkage cooking ( % ) and texture or tenderness (N) . Each treatment was replicated 3 times. The data were analyzed using analysis of variance, if there is a difference then performed Duncan 's Multiple Range Test. The results showed that the physical quality of fresh beef sold in the traditional market traders Poncokusumo Distric of Malang Regency still eligible or safety standards for the fresh cow. It had the following properties: water content of 76.53 %, pH of 5.62; cooking loss or shrinkage of 24.60 %, WHC of 37.10 % and texture or tenderness 23.84 N. Key words: physical quality, beef, traditional market